Scientific evidence of prophetic medicine: exploring its role in integrative medicine – a review and bibliometric analysis - Awang, Anis Fadhlina Izyani; Zakaria, Nor Hafizah; Sheikh Mohamed, Hassan Ibrahim; Abdul Majid, Fadzilah Adibah (International Islamic University Malaysia, 2025)
Prophetic medicine embodies teachings by Prophet Mohammad صلى الله عليه وسلم regarding health and well-being. Despite its historical significance, there is a growing global interest in traditional medicine in the context of modern medicine, necessitating a comprehensive and critical analysis of its relevance today. This study aimed to evaluate the scientific landscape and research trends surrounding prophetic medicine through a bibliometric approach, complemented by a review of recent evidence on key natural remedies. Literature from the Scopus database was retrieved using relevant keywords. Inclusion and exclusion criteria were applied, with the final selection of 171 articles for bibliometric analysis using VOSviewer software. The analysis identified 15 authors, 9 countries, 15 journals, 14 documents, and 157 keywords that fulfilled the chosen threshold. Although article publication fluctuated over the years, an upward trend emerged, with rapid growth from 2022 to 2023, reflecting the recent surge in scholarly attention. Salah Mohamed El Sayed was identified as the most prolific author, while Evidence-based Complementary and Alternative Medicine was the leading journal. Saudi Arabia emerged as a recent key contributor to prophetic medicine research and had the closest collaboration with Malaysia. Common research hotspots included “black cumin” and “antioxidant activity,” with recent interest focusing on honey and olives. The bibliometric findings highlight the novelty of this study by quantitatively mapping the current research landscape, identifying gaps, and highlighting emerging areas of focus. This review also integrates scientific evidence supporting the bioefficacy of prophetic remedies, reinforcing their relevance as complementary components of integrative medicine. The findings encourage further in-depth investigations to substantiate their therapeutic benefits.